Analisis Perumusan Strategi Bisnis: Studi pada Andhika Salon Cibubur - D. Bernadine (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
Salon Andhika is a beauty salon that offers beauty treatments for hair, facial skin, and the body. With various types of treatments offered and unique services, making customers feel calm and comfortable with satisfactory results after the treatment. The purpose of this study was to find out the most appropriate strategy for Salon Andhika in facing current competition by paying attention to internal and external environmental conditions. major competitors and consumers. The type of research used is descriptive and uses qualitative data. The analysis method used in this research is External Factor Evaluation (EFE) Matrix, Competitive Profile Matrix (CPM), Internal Factor Evaluation (IFE) Matrix, Internal-External (IE) Matrix, Strategic Position And Action Evaluation (SPACE) Matrix, SWOT. Matrix, and QSPM. The results showed that there were two alternative strategies recommended, namely the Product Development Strategy and the Market Penetration Strategy. The Product Development Strategy is the most appropriate decision result for the company with a total score of attractiveness (TAS) of 5.92, which is greater than the Market Penetration Strategy which has a total score of attractiveness (TAS) of 5.22. Product development can be executed by developing new service salon home service s and buying more renewable supplies & equipment. Keywords: IFE Matrix, EFE Matrix, CPM, SWOT Matrix, I-EMatrix, QSPM.